2022
DOI: 10.1590/s1677-5538.ibju.2021.0383
|View full text |Cite
|
Sign up to set email alerts
|

Can concomitant bladder neck incision and primary valve ablation reduce early re-admission rate and secondary intervention?

Abstract: Objective: To assess the effect of bladder neck morphology and its incision (BNI) in patients with posterior urethral valve (PUV) on early reintervention rate. Patients and methods: Infants undergoing PUV ablation (PVA) before 24 months of age and had at least 18 months of follow-up, were categorized into three groups according to the bladder neck appearance on baseline radiological and endoscopic examination: group 1; normal bladder neck underwent PVA, group 2; high bladder neck underwent PVA plus BNI, group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The availability of useful indices could be vital in selecting pediatric conditions. Bladder neck incision in children previously treated for posterior urethral valves has often relied on anatomical appearance rather than videourodynamics 21 . Establishment of valid indices of obstruction and contractility might avoid potentially unindicated interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of useful indices could be vital in selecting pediatric conditions. Bladder neck incision in children previously treated for posterior urethral valves has often relied on anatomical appearance rather than videourodynamics 21 . Establishment of valid indices of obstruction and contractility might avoid potentially unindicated interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder neck incision in children previously treated for posterior urethral valves has often relied on anatomical appearance rather than videourodynamics. 21 Establishment of valid indices of obstruction and contractility might avoid potentially unindicated interventions. While uncommon, primary bladder neck obstruction has been described in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Abdelhalim and colleagues from Egypt performed in page 485 the paper that is the cover in this edition (6). In this paper the authors assess the effect of bladder neck morphology and its incision (BNI) in patients with posterior urethral valve (PUV) on early reintervention rate and concluded that in morphologically high bladder neck associated PUV, concomitant BNI with posterior valve ablation doesn't reduce early re-intervention rate.…”
mentioning
confidence: 99%